Sensitivity rates of bacteria causing urinary tract infections to commonly used antibiotics - Ning Rintiswati Ning Rintiswati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: The choice of antibiotics in the treatment of infections, including urinary tract infection has been mainly based on previous clinical and empirical experiences. No antibiotic guideline is available for use in daily practice so that failure in the treatment of infections will inevitably happen. Since it is quite complicated work to prepare the guideline we start with a simple preliminary study on antibiotic susceptibility of bacteria causing urinary tract infections.Objectives: The aim of this study is to know the recent status of various antibiotics agent in relation to their efficacy in the treatment of urinary tractus infection, especially in Yogyakarta.Methods: Isolation, identification and antibiotic susceptibility test of bacteria from urine specimens were performed by available standard methods. Subject: Urine specimens sent to Microbiology Department for isolation, identification, and antibiotics susceptibility test.Results: The results showed that 184 isolates were obtained during the period of July 1997 to June 1998. Susceptibility rate of the isolates to ampicillin was very low, whereas the rates were much higher for ciprofloxacin, norfloxacin, gentamicin, and amikacin.Conclusions: It is concluded that ciprofloxacin could be the first choice and norfloxacin, gentamicin or amikacin serve as alternatives in the treatment of urinary tract infections.Key words: bacteria - urinary tract infection - antibiotics suceptibility - sensitivity rates